MEMS based antenna of energy harvester for wireless sensor node - Mohd Yunus N.H.; Sampe J.; Yunas J.; Pawi A.; Rhazali Z.A. (Springer, 2023)
Electric rectifiers; Energy harvesting; Glass; Metal analysis; Microwave antennas; Omnidirectional antennas; Rectennas; Sensor nodes; Slot antennas; Surface micromachining; Wave propagation; Antenna substrates; Experimental validations; Micromachined antenna; Micromachining process; Omnidirectional radiation pattern; Rf energy harvesters; RF energy harvesting; Wireless sensor node; Directional patterns (antenna)